2018
DOI: 10.3390/medsci6030072
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Adolescence

Abstract: Adolescent insomnia is a common condition that negatively impacts a developing young adult’s mental and physical health. While the treatment of adult insomnia has been standardized, the treatment of pediatric insomnia is very practitioner-dependent and few large-scale studies are available to determine a standard recommended practice. There is great hope that as the adolescent medicine and sleep medicine fields flourish, larger cohort analyses will be performed to determine the prevalence and precipitating fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 90 publications
1
17
0
1
Order By: Relevance
“…Insufficient adolescent sleep could be of great concern, as literature has shown that behaviorally decreased sleep and weekend oversleep may lead to suicidal tendencies independently of depression existence [ 51 ]. Qualitative sleep is of great importance for children and adolescents as, apart from its biological role, it is highly related to learning ability, memory and school performance [ 52 , 53 ]. High-quality sleep is characterized by no nighttime disturbances such as sleep interruption, daytime dysfunction and issues such as bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient adolescent sleep could be of great concern, as literature has shown that behaviorally decreased sleep and weekend oversleep may lead to suicidal tendencies independently of depression existence [ 51 ]. Qualitative sleep is of great importance for children and adolescents as, apart from its biological role, it is highly related to learning ability, memory and school performance [ 52 , 53 ]. High-quality sleep is characterized by no nighttime disturbances such as sleep interruption, daytime dysfunction and issues such as bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…High ED intake is also associated with unhealthy behavior, such as reduced and insufficient sleep and breakfast skipping in adolescents [ 7 , 17 , 21 , 22 , 23 , 24 ]. Evidence shows that 30 to 50% of adolescents sleep less than recommended 8 h [ 25 , 26 , 27 ], and the prevalence of sleep problems varies between 10 to 20% in adolescents [ 28 , 29 , 30 ]. According to the large studies conducted in Europe and other countries [ 31 , 32 , 33 , 34 , 35 ], a high proportion of adolescents were classified as breakfast-skippers, ranging from 40–50% (China, Austria, Slovenia) to 10–20% (Spain, Poland, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 5 ] Declining physical exercise, overutilization of gadgets during bedtime affects the sleep quality thereby predisposing to rise of depression. [ 3 5 ] A number of literatures have also shown that sleep deprivation and depression both have bidirectional relationship. [ 6 7 8 9 ] Depression can have affect on the academic performances of students, hence limiting their career opportunities.…”
Section: Introductionmentioning
confidence: 99%